Cycling above rather than below lactate threshold is more effective for nitric oxide release and post-exercise blood pressure reduction in individuals with type-2 diabetes - Ricardo Yukio Asano; Rodrigo Alberto Vieira Browne; Rafael da Costa Sotero; Marcelo Magalhães Sales; José Fernando Vila Nova de Moraes; Carmen Sílvia Grubert Campbell; Herbert Gustavo Simões (Motriz: Revista de Educacao Fisica, 2013)
The purposes of this study were to analyze and compare the effects of exercise performed in different intensities, above and below lactate threshold (LT) on post-exercise blood pressure (BP) and nitric oxide (NO) responses in individuals with type 2 diabetes (T2D). For this, 11 T2D underwent the following sessions: 1) control session; 2) 20-min of moderate cycling (80% LT); and 3) 20-min of high intensity cycling (120%LT) on a cycle ergometer. Plasma NO and BP measurements were carried out at rest and at 15 and 45 min of post-sessions. When compared to rest, only the exercise session performed at 120%LT elicited an increase of NO (from 7.2 to 9.5 µM, p<0.05), as well as a decrease in systolic BP (from 126.6±7.9 to 118.7±3.9 mmHg, p<0.05) during the post-exercise period. In conclusion, the results suggest that NO release and post-exercise BP decrease are intensity-dependent for individuals with T2D.